2010
DOI: 10.1039/c0cc01091j
|View full text |Cite
|
Sign up to set email alerts
|

Greatly facilitated oxygen vacancy formation in ceria nanocrystallites

Abstract: The formation of oxygen vacancies in nanoparticles Ce(n)O(2n) (n < or = 80), studied using density-functional calculations, is found to be greatly facilitated compared to extended surfaces, which explains the observed spectacular reactivity of nanostructured ceria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
226
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(239 citation statements)
references
References 27 publications
10
226
2
1
Order By: Relevance
“…In this regard, undoped TiO 2 should not be a very good catalyst since the formation energy of an oxygen vacancy in the (110) surface is 3.66 eV from DFT+U 40,41 , however an energy from periodic B3-LYP studies was not given 41,42 . It is possible that small clusters of TiO 2 could be 30 more favourable for oxygen vacancy formation, as it is generally the case that small clusters are more reactive than their bulk counterpart; this has been discussed for ceria clusters recently 43 . We determine stable adsorption configurations for the TiO 2 35 clusters on the rutile (110) surface and study the electronic properties of these structures as well as their reactivity in terms of oxygen vacancy formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, undoped TiO 2 should not be a very good catalyst since the formation energy of an oxygen vacancy in the (110) surface is 3.66 eV from DFT+U 40,41 , however an energy from periodic B3-LYP studies was not given 41,42 . It is possible that small clusters of TiO 2 could be 30 more favourable for oxygen vacancy formation, as it is generally the case that small clusters are more reactive than their bulk counterpart; this has been discussed for ceria clusters recently 43 . We determine stable adsorption configurations for the TiO 2 35 clusters on the rutile (110) surface and study the electronic properties of these structures as well as their reactivity in terms of oxygen vacancy formation.…”
Section: Introductionmentioning
confidence: 99%
“…To model the rutile (110) surface, we use a three dimensional periodic slab model and a plane wave basis set to describe the valence electronic wave functions within the VASP code 43 . The cut-off for the kinetic energy is 396 eV.…”
mentioning
confidence: 99%
“…We may only speculate that a relatively higher intensity of the 1108 cm -1 band on particles, commonly assigned to methoxy in atop geometry and which, on the basis of DFT calculations [21], is less stable compared to adsorption on oxygen vacancy, would be consistent with the methanol adsorption on low-coordinated Ce sites present on the particle edges. In addition, the energy of formation of an oxygen vacancy on the surfaces of nanoparticles has been shown to be significantly lower than that of planar surfaces, which leads to much higher oxygen-vacancy concentrations in the nanoparticles, and this property is strongly dependent upon size for small particles [7][8][9]. Moreover, the most energetically favored oxygen vacancies are created at edge sites [8].…”
Section: Figurementioning
confidence: 99%
“…In the case of ceria, density functional theory (DFT) calculations have shown that the formation of an oxygen vacancy is energetically favored on the surfaces of ceria nanoparticles in comparison to extended ceria surfaces [7][8][9]. Indeed, experimental studies have revealed that nanoparticles of ceria have the capacity to support a high concentration of defects and reduced species, which are present in only minute quantities on planar surfaces [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Cerium dioxide nanoparticles have been shown to have better catalytic performance than bulk material but the detailed mechanism of oxygen buffering is relatively poorly understood. Nanoparticle surfaces are thought to play an important role but prediction of surface configurations in this system using density functional theory, is not straightforward [3]. Atomic force microscopy can provide experimental verification of theoretically predicted structures for bulk single crystals [4] but it has not previously been possible to determine the surface chemistry of active oxide nanoparticles experimentally [5].…”
mentioning
confidence: 99%